(untitled) (INTERNATIONAL SEMINAR, 2024)
This literature review addresses the relationship between translation ability and the neural mechanisms underlying the cognitive processes involved in translation. Drawing on recent developments in neuroscience, we examine how different brain regions contribute to the complex tasks of understanding, producing and integrating cultural nuances. We highlight key studies using neuroimaging techniques such as fMRI and EEG that demonstrate the dynamic interplay between linguistic and cognitive functions during translation activities. We also discuss the implications of bilingualism and multilingualism for neural plasticity and cognitive flexibility, focusing on how these factors enhance translation ability. This literature review employs a systematic approach, including a keyword-based search across academic databases, strict inclusion and exclusion criteria, and thematic synthesis of findings, to analyze the cognitive and neural mechanisms underlying translation. In this review, we synthesize findings from cognitive psychology, linguistics and neuroscience to provide a comprehensive picture of how translation ability is acquired not only through practice but is also deeply rooted in brain architecture. Finally, we suggest some avenues that future research can take to gain a deeper understanding of the neural correlates of translation with a view to informing pedagogical approaches in translation training.